Lithospheric electrical structure across the Bangong-Nujiang Suture in northern tibet revealed by magnetotelluric - Yang, Zhen; Liang, Hongda; Gao, Rui; Han, Jiangtao; Xin, Zhonghua; Kang, Jianqiang; Shi, Zhuoxuan; Zhang, Lu; Qi, Rui; Li, Huilin (Frontiers in Earth Science, 2023)
Competing hypotheses have been proposed to explain the subduction polarity of the Bangong-Nujiang Tethyan Ocean and the formation of the high-conductivity anomaly beneath the Qiangtang terrane. However, the lithospheric architecture of the northern Tibetan Plateau is still poorly understood due to inhospitable environments and topography. Therefore, in the winter of 2021, a 440 km long, SN-trending broadband magnetotelluric (MT) profile was recorded in northern Tibet to detect its regional lithospheric structure. The nonlinear conjugate gradients algorithm is conducted to invert the individual TM mode data. A reliable 2D electrical model was obtained by ablation processing and analysis of broadband magnetotelluric data to test the lithospheric electrical structure and dynamics between the northern Lhasa and Qiangtang terranes. The inversion results reveal the lithospheric structure at a depth of 100 km in northern Tibet, which synthesizes geological, geochemical and deep seismic reflection evidence and firmly identifies that the trace of the south-dipping conductor mainly resulted from the southward subduction of the Bangong-Nujiang Tethyan Ocean under the Lhasa terrane and the trace of the north-dipping conductor likely due to the northward subduction of the Bangong-Nujiang Tethyan Ocean under the Qiangtang terrane. In addition, the magnetotelluric profile also images a high-conductivity lithospheric-scale anticline beneath the central Qiangtang terrane, which may correspond to the upwelling of postcollisional magmatism triggered by northward subduction of the Bangong-Nujiang Tethyan Ocean under the Qiangtang terrane, aqueous fluid and/or partial melting.